Managing politics and conflict in projects - Irwin, Brian, 1967 Dec 21- (Management Concepts, 2008)
A guide that walks you through the 'soft' issues of project management, including communicating, negotiating, and influencing skills that are vital to your project success. It helps you to understand your organization's political climate and culture and ascend the corporate ladder to the next level as a project manager.
Title from title screen.
Keywords: Management -- Study and teaching.; elektronické knihy; electronic books